Near-infrared light-transmitting dimming material capable of adjusting shielding wavelength and preparation method of near-infrared light-transmitting dimming material

By introducing shielding composites of polymer quantum dots and nanocesium tungsten bronze into the light-transmissible material, and forming a clad structure through silane coupling agent modification treatment and controlled degradation preparation technology for polyvinyl alcohol aqueous solution, the problems of poor flexibility and insufficient dispersion in flexible wearable devices are solved, and efficient visible light shielding and near-infrared transmission properties are achieved.

CN119823555APending Publication Date: 2025-04-15ZERO DIMENSION (NINGBO) TECH DEV CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510071282.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing light-transmitting materials have poor flexibility, fragility and difficulty in processing in scenarios such as flexible wearable devices, and the compatibility and dispersion between inorganic functional materials and organic resin matrix are insufficient, resulting in limited improvement in overall performance.

Method used

By introducing shielded composites of polymer quantum dots and nanocesium tungsten bronze, combined with silane coupling agent modification treatment and controlled degradation preparation technology for polyvinyl alcohol aqueous solution, a cladding structure is formed to improve the dispersion and stability of the material.

Benefits of technology

It achieves high visible light shielding performance and flexible and adjustable near-infrared transmission performance, overcomes the problem of uneven dispersion of traditional inorganic materials easily agglomerated and dispersed, and improves the optical uniformity and long-term use stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823555A_ABST
    Figure CN119823555A_ABST
Patent Text Reader

Abstract

The invention relates to a near-infrared light-transmitting dimming material capable of adjusting shielding wavelength and a preparation method thereof, and the light-transmitting dimming material comprises the following components in parts by weight: 97.5-99.1 parts of matrix resin, 0.5-1.5 parts of a shielding compound and 0.4-1 part of an auxiliary agent, the shielding compound comprises polymer quantum dots and nano cesium tungsten bronze, and the mass ratio of the polymer quantum dots to the nano cesium tungsten bronze is 1: (0.01-0.5); the visible light transmittance of the light-transmitting dimming material is 30% or below, the near-infrared light transmittance is 45% or above, and the initial transmission wavelength can be adjusted from 700 nm to 1200 nm. The light-transmitting dimming material disclosed by the invention is low in transmittance in a visible light wavelength range, high in transmittance in a near infrared ray wavelength range and excellent in processability and optical adjustability, can be used as a filtering material for infrared sensors, infrared cameras and the like, or is suitable for applications such as automobiles, intelligent household appliances and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of light-transmitting materials, and in particular to a near-infrared light-transmitting dimming material capable of adjusting shielding wavelength and a preparation method thereof. Background Art

[0002] The global near-infrared light-transmitting material market has shown a rapid growth trend in recent years, with major application areas including consumer electronics, automotive electronics, industry, and medical treatment. Infrared sensors, infrared cameras, infrared radars, etc. have been effectively applied in a wide range of technical fields. For example, in information and communication terminal applications such as smartphones and security inspection equipment, facial recognition has been introduced, and infrared sensors or infrared cameras are used to detect the correct facial shape. In addition, in the automotive field, in order to detect the surrounding conditions of the vehicle, on-board infrared cameras or infrared radars are installed on the vehicle. In order to timely and correctly feedback the detection information and avoid interference from other wavelengths such as visible light transmission, high-precision and high-accuracy near-infrared light-transmitting equipment is required to transmit only near-infrared light.

[0003] Traditional inorganic materials such as metal oxides, silicon-based semiconductors and chalcogenide glasses have good near-infrared transmittance, but have problems such as poor flexibility, fragility and difficulty in processing, and are not suitable for scenes with high requirements for flexibility and processability, such as flexible wearable devices. For example, invention CN118026525A discloses a near-infrared transparent black optical glass and its application, wherein the black optical glass is composed of oxide glass and a coloring component, and the coloring component includes the following components in terms of the mass percentage of the coloring component to the oxide glass: Cr2O3: 0.15% to 0.25%; CoO: 0.05% to 0.10%; CeO2: 1% to 5%; MnO2: 0 to 1%. The black optical glass of the invention adopts a specific content of coloring components, can absorb ultraviolet, visible and far infrared bands, and maintains excellent transmittance in the near infrared, especially at a wavelength of 905nm, and has clear transmittance to the target band.

[0004] Organic materials have flexibility and adjustable optical properties, but most organic molecules have a narrow absorption range, making it difficult to achieve comprehensive elimination of light interference in the UV-visible region. There is also a trade-off between the thickness and transmittance of the material. Although increasing the content of organic molecules can reduce the interference of visible light, it will also lead to a decrease in near-infrared transmittance and an increase in film thickness. The main research and development path is to form a composite material of organic and inorganic materials and give full play to the advantages of both. For example, invention CN117940377A discloses a manganese oxide, manganese oxide particles, near-infrared transmission material and near-infrared transmission film, wherein the constituent elements of the manganese oxide are expressed as A-Mn-O, and the constituent element A is one or more elements selected from H, alkali metals, alkaline earth metals, rare earth elements, Be, Mg, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Re, Fe, Ru, Co, Os, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, Sb, Bi, S, Se, Te, F, Cl, Br, and I. The invention also uses a resin dispersion to obtain a near-infrared transmission material and a near-infrared transmission film, which can avoid visible light transmission as much as possible and transmit near-infrared light.

[0005] The near-infrared transmission performance and visible light shielding performance of the above-mentioned materials are mainly achieved through metal oxides, which have low adjustability and are prone to lose sight of one thing while focusing on the other. In addition, the technical field of light-transmitting materials has high requirements for the uniformity and stability of materials. The compatibility and dispersibility between inorganic materials such as metal oxides and organic resin matrices are important factors that restrict the improvement of the comprehensive performance of light-transmitting composite materials. Therefore, how to improve the compatibility, dispersibility and formula designability of inorganic functional materials in organic resin matrices, so as to provide a high-performance light-transmitting material that can maintain excellent visible light shielding performance and has efficient and flexible near-infrared transmittance, is a problem that needs to be solved urgently by technicians in this field. Summary of the invention

[0006] In view of the defects existing in the above-mentioned prior art, the present invention provides a near-infrared translucent dimming material with adjustable shielding wavelength and a preparation method thereof. The translucent dimming material provides high visible light shielding performance and flexible and adjustable near-infrared transmittance by introducing a shielding compound of polymer quantum dots and nano-cesium tungsten bronze, and the preparation process is simple, thus overcoming the problem that traditional inorganic materials are prone to agglomeration and uneven dispersion, resulting in reduced comprehensive performance of composite materials.

[0007] In a first aspect, the present invention provides a near-infrared light-transmitting dimming material with adjustable shielding wavelength, wherein the light-transmitting dimming material comprises:

[0008] Base resin 97.5~99.1 parts

[0009] Shielding compound 0.5-1.5 parts

[0010] Additives 0.4~1 part

[0011] The shielding compound comprises polymer quantum dots and nano-cesium tungsten bronze, and the mass ratio of the polymer quantum dots to the nano-cesium tungsten bronze is 1:(0.01-0.5);

[0012] The visible light transmittance of the light-transmitting dimming material is below 30%, the near-infrared light transmittance is above 45%, and the initial transmission wavelength is adjustable from 700nm to 1200nm.

[0013] The light-transmitting dimming material of the present invention has good visible light shielding performance and near-infrared light transmission performance as a whole by introducing a shielding compound of polymer quantum dots and nano-cesium tungsten bronze, effectively reducing the interference of visible light on near-infrared light, and by adjusting the ratio of polymer quantum dots and nano-cesium tungsten bronze, the selection of shielding wavelength range is achieved, thereby adjusting the near-infrared transmission performance and visible light shielding performance. Among them, polymer quantum dots utilize the quantum confinement effect to efficiently absorb visible light while maintaining high transmittance to near-infrared light. The modified nano-cesium tungsten bronze, through its excellent optical properties, efficiently demonstrates the adjustability of near-infrared transmission performance and visible light shielding performance.

[0014] The mass ratio of polymer quantum dots to nano-cesium tungsten bronze is set at 1:(0.01-0.5), which can optimize the synergistic regulating effect of the two on the shielding wavelength, ensure the balance between near-infrared transmittance and visible light shielding performance, so that the visible light transmittance is below 30%, preferably below 10%, the near-infrared light transmittance is above 45%, preferably above 70%, more preferably above 80%, and the initial transmission wavelength is adjustable from 700nm to 1200nm, preferably from 700nm to 1000nm.

[0015] The initial transmission wavelength represents the critical wavelength for light transmission. When it is less than this wavelength, the transmittance of light is below 30%, preferably below 10%, and more preferably substantially opaque. Taking the filter product used in the near-infrared sensor as an example, the light-transmitting dimming material of the present invention ensures that external visible light will not enter and interfere with the sensor, and only near-infrared light in a specific wavelength range is detected by the sensor, ensuring the detection accuracy. The initial transmission wavelength can be reasonably set and regulated according to the material composition and ratio of the material. If the initial transmission wavelength value is set too low, a large amount of visible light with a longer wavelength will be transmitted, interfering with the transmission and detection of near-infrared light; if the initial transmission wavelength is set too high, it is easy to cause the near-infrared light with a shorter wavelength to be unable to transmit, affecting the overall transmittance of the near-infrared light. Therefore, setting the initial transmission wavelength within a reasonable range according to actual needs has important technical significance and practical needs.

[0016] Nano cesium tungsten bronze (Cs x WO3) has good near-infrared absorption, but its surface activity is high, and it is prone to agglomeration, resulting in poor dispersibility in the matrix resin and uneven optical properties. Therefore, based on the above ratio, if the content of nano cesium tungsten bronze is too high and the content of polymer quantum dots with good dispersibility is too low, on the one hand, it is easy to cause the dispersibility of the shielding composite in the matrix resin to deteriorate, and the comprehensive performance of the light-transmitting and light-adjusting material is prone to be uneven and unstable. On the other hand, too high a content of nano cesium tungsten bronze will cause the overall visible light shielding and near-infrared transmittance of the material to decrease too much, and a large amount of transmitted visible light is likely to interfere with the near-infrared light transmittance and near-infrared detection results of the material, unable to meet the application requirements. If there are too many polymer quantum dots in the above ratio, although the overall visible light shielding and near-infrared transmittance of the material are good, the light-adjusting performance of the material cannot be demonstrated, which is likely to restrict the application range of the material.

[0017] Preferably, the matrix resin includes at least one of PP, PMMA, and PC; the additives include an antioxidant and a lubricant, and the mass ratio of the antioxidant to the lubricant is (1-3):1.

[0018] As the matrix resin, there is no particular limitation on the type of resin, and resins that can be formed into the desired shape can be used. For example, thermoplastic resins, thermosetting resins, radiation-curable resins, and two-component mixed-curable resins can be used. Among them, from the perspective of the convenience of forming processing, it is preferred to use thermoplastic resins as the matrix resin. Specific thermoplastic resins include, but are not limited to: polyolefin resins such as polyethylene and polypropylene (PP), polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polycarbonate resin (PC), polyacrylic acid or its esters, poly(methacrylic acid) or its esters, etc. polyacrylic acid-based resins (such as PMMA), polyvinyl-based resins such as polystyrene and polyvinyl chloride, cellulose-based resins such as triacetyl cellulose, and urethane resins such as polyurethane. Considering the transparency, mechanical properties, and production cost of the matrix resin comprehensively, at least one of PP, PMMA, and PC is preferred.

[0019] The antioxidant includes at least one of antioxidant 1076, antioxidant 1098, and antioxidant 168; the lubricant includes at least one of calcium stearate, zinc stearate, and magnesium stearate.

[0020] Preferably, the chemical formula of nano cesium tungsten bronze is CsxWO3, 0 < x ≤ 0.33, and the particle size is 10-50 nm;

[0021] The nano cesium tungsten bronze can be optionally modified by a silane coupling agent.

[0022] Preferably, the polymer quantum dots are prepared by controlled degradation of polyvinyl alcohol aqueous solution, and the particle size is below 5 nm;

[0023] The nano cesium tungsten bronze is modified by a silane coupling agent;

[0024] The polymer quantum dots and the modified nano-cesium tungsten bronze are mixed evenly to obtain the shielding compound.

[0025] It is a simple and effective method to prepare polymer quantum dots and modified nano-cesium tungsten bronze separately, mix the two in proportion to obtain a shielding compound, and then blend it with a matrix resin for molding.

[0026] Nano-cesium tungsten bronze has good near-infrared absorption performance, but its surface activity is high, and it is easy to agglomerate in the composite material, resulting in poor dispersibility, and ultimately uneven shielding performance. In order to avoid the defects of traditional inorganic nanoparticles that are easy to agglomerate and have uneven performance, the nano-cesium tungsten bronze of the present invention is preferably modified by a silane coupling agent, and the silane coupling agent is selected from at least one of KH-550, KH-560, KH-570, KH-580, KH-590, KH-602, KH-902, KH-903, and KH-792, preferably aminosilane coupling, KH-550, KH-602, and KH-792.

[0027] The particle size of polymer quantum dots is preferably controlled below 5nm, mainly to improve its optical properties and dispersion effect in light-transmitting dimming materials. The preparation of quantum dots through the controlled degradation of polyvinyl alcohol (PVA) aqueous solution can not only ensure the miniaturization of the particle size, but also make the surface of the quantum dots have better compatibility, so that they are evenly dispersed in the matrix. Quantum dots with a particle size less than 5nm have a more significant quantum confinement effect, maintain a high visible light shielding performance, and can accurately control the transmission / absorption performance of near-infrared light. If the particle size exceeds 5nm, the quantum confinement effect of the polymer quantum dots is weakened, the visible light shielding performance and near-infrared transmission performance may decrease, and a larger particle size may cause aggregation between particles, affecting the optical uniformity and long-term stability of the material, and weakening the overall performance.

[0028] Preferably, the shielding compound comprises a coating structure formed by coating polymer quantum dots on the surface of nano-cesium tungsten bronze, and the coating structure is obtained by the following steps:

[0029] Dispersing nano-cesium tungsten bronze in polyvinyl alcohol aqueous solution;

[0030] The polymer quantum dots prepared by the controlled degradation of polyvinyl alcohol aqueous solution are in-situ coated on the surface of nano-cesium tungsten bronze to obtain the coated structure.

[0031] Since the compatibility and dispersibility of nano-cesium tungsten bronze in the matrix resin are poor, the present invention uses polymer quantum dots to coat the surface of cesium tungsten bronze particles to form a coating structure, which can effectively reduce the interaction between cesium tungsten bronze particles and prevent agglomeration. This coating also greatly improves the interface compatibility between the shielding compound as a whole and the matrix resin (such as PP, PMMA, PC), thereby ensuring the uniform distribution of particles in the matrix.

[0032] Secondly, the coating of nano-cesium tungsten bronze with polymer quantum dots can not only improve the dispersibility of cesium tungsten bronze, but also form a protective layer to prevent chemical degradation or structural instability of cesium tungsten bronze particles in complex environments such as high temperature and humidity. In addition, the particle size of the coating structure is preferably controlled below 100nm, with a high surface area to volume ratio, which can better interact with the matrix and improve the overall mechanical strength and thermal stability of the composite material. This stability is particularly critical for practical industrial applications, especially under complex optical and environmental conditions.

[0033] Preferably, a silane coupling agent modified layer is formed on the surface of the coating structure. This structural design further improves the dispersibility and stability of the shielding compound in the matrix, ensuring that the dimming material has higher optical uniformity and long-term reliability.

[0034] In a second aspect, the present invention further provides a method for preparing the light-transmitting dimming material, comprising the following steps:

[0035] S1: preparing a shielding compound;

[0036] S2: mixing the base resin, the additive and the shielding compound to obtain a premix;

[0037] S3: adding the premixed material into an extruder, and performing melt extrusion molding to obtain the light-transmitting dimming material.

[0038] The shape and size of the light-transmitting dimming material formed by melt extrusion can be selected in many ways according to actual needs, such as film, sheet, three-dimensional profile, etc. In practical applications, sheets with a thickness of 0.5 to 3 mm are widely used.

[0039] Preferably, S1 comprises the following steps:

[0040] Step 1, dissolving PVA in deionized water to obtain a clear and transparent PVA solution;

[0041] Step 2: Add the PVA solution into a high-pressure reactor, seal the reactor and place it in a muffle furnace, heat it to 200-250° C., react isothermally for 5-8 hours and then cool it down;

[0042] Step 3: Concentrating and drying by rotary evaporator to obtain polymer quantum dot powder;

[0043] Step 4: using a silane coupling agent to modify the nano-cesium tungsten bronze;

[0044] Step 5: Evenly mix the polymer quantum dots and the modified nano-cesium tungsten bronze to obtain the shielding compound.

[0045] Regarding the blending and compounding method, polymer quantum dots and modified nano-cesium tungsten bronze are prepared separately, and then the two are mixed in proportion to obtain a shielding compound, which is efficient and simple.

[0046] Preferably, in the shielding compound, the polymer quantum dots cover at least a portion of the nano-cesium tungsten bronze, and S1 comprises the following steps:

[0047] Step 1, dissolving PVA in deionized water to obtain a clear and transparent PVA solution;

[0048] Step 2: Add nano-cesium tungsten bronze to the PVA solution, stir evenly, add the solution to a high-pressure reactor, seal the reactor, place it in a muffle furnace, heat it to 200-250° C., react isothermally for 5-8 hours, and then cool it down;

[0049] Step 3: Concentrate and dry by rotary evaporator to obtain a shielding compound, wherein the shielding compound includes a coating structure formed by in-situ coating of polymer quantum dots on the surface of nano-cesium tungsten bronze.

[0050] Preferably, in step 2, the temperature is raised to 200-250° C. at a rate of 2-5° C. / min.

[0051] In order to effectively form a coating structure of polymer quantum dots on nano-cesium tungsten bronze at the nanometer scale, the present invention adopts an in-situ deposition coating method to form a relatively uniform coating structure. By controlling the heating rate, reaction temperature and time in the muffle furnace, the particle size and performance of the polymer quantum dots are controlled so that they can be controlled to have different absorption wavelength characteristics.

[0052] Preferably, the cooling process in step 2 further includes adding a silane coupling agent at 60-70° C. and mixing and reacting the mixture so that a silane coupling agent modified layer is formed on the surface of the coating structure.

[0053] By utilizing the cooling process after the reaction, a silane coupling agent is added at an appropriate temperature to further improve the matrix compatibility and dispersibility of the coating structure.

[0054] The present invention has at least the following beneficial effects:

[0055] (1) The present invention introduces a shielding compound design of polymer quantum dots and modified nano-cesium tungsten bronze, utilizes the quantum confinement effect of polymer quantum dots to provide excellent visible light shielding and near-infrared transmittance, and achieves the effect of adjusting optical performance through the shielding performance of modified nano-cesium tungsten bronze against near-infrared light. This design realizes that the light-transmitting dimming material maintains the visible light transmittance below 30%, preferably below 10%, and the near-infrared light transmittance above 45%, preferably above 70%, and more preferably above 80%, and can flexibly adjust the optical performance such as the shielding wavelength range according to the needs, meeting the application needs of various scenarios.

[0056] (2) The present invention significantly improves the dispersibility of the shielding compound in the matrix through the coating effect of polymer quantum dots and the synergistic modification of silane coupling agents, effectively avoiding the performance unevenness problem caused by agglomeration of traditional inorganic particles, giving the dimming material higher optical uniformity and long-term stability, and ensuring its reliable performance in a variety of complex environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a TEM photo of polymer quantum dots in Example 1 of the present invention;

[0058] Figure 2 is the transmittance curve of Example 1 of the present invention;

[0059] Figure 3 is the transmittance curve of Example 6 of the present invention;

[0060] Figure 4 This is the transmittance curve of Example 7 of the present invention. DETAILED DESCRIPTION

[0061] In order to better understand the above technical solution, the above technical solution will be described in detail below in combination with the specification and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0062] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0063] It should also be noted that the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, such that a commodity or device comprising a series of elements not only includes those elements but also includes other elements not expressly listed, or further includes elements inherent to such commodity or device. Without further limitation, an element defined by the statement "comprising one..." does not exclude the presence of additional identical elements in the commodity or device comprising said element.

[0064] An adjustable shielding wavelength near-infrared light-transmitting dimming material, with a visible light transmittance of less than 30%, preferably less than 10%, a near-infrared light transmittance of more than 45%, preferably more than 70%, more preferably more than 80%, and an initial transmittance wavelength adjustable from 700 nm to 1200 nm, preferably adjustable from 700 nm to 1000 nm. By weight, the raw materials of the light-transmitting dimming material specifically include:

[0065] (1) Matrix resin, 97.5 - 99.1 parts, preferably including at least one of PP, PMMA, and PC;

[0066] (2) Shielding complex, 0.5 - 1.5 parts, including polymer quantum dots and nano cesium tungsten bronze with a mass ratio of 1:(0.01 - 0.5). The shielding complex is mainly obtained in two ways:

[0067] 2.1 Ordinary mixing, with simple operation and easy control of dosage. Prepare polymer quantum dots and modified nano cesium tungsten bronze separately, and then mix the polymer quantum dots and the modified nano cesium tungsten bronze evenly to obtain the shielding complex. Among them, the polymer quantum dots are prepared by controllable degradation of an aqueous solution of polyvinyl alcohol, with a particle size of less than 5 nm, which can be referred to in the appendix Figure 1 ;

[0068] The nano cesium tungsten bronze (chemical formula Cs x WO3, 0 < x ≤ 0.33), with a particle size of 10 - 50 nm; the nano cesium tungsten bronze is modified by a silane coupling agent, and the silane coupling agent is selected from at least one of KH-550, KH-560, KH-570, KH-580, KH-590, KH-602, KH-902, KH-903, and KH-792, preferably amino silane coupling, one or more of KH-550, KH-602, and KH-792.

[0069] 2.2 Coating structure, with excellent performance. The shielding complex includes a coating structure formed by polymer quantum dots coating on the surface of nano cesium tungsten bronze. As a preference, the particle size of the coating structure is less than 100 nm, and it is obtained through the following steps:

[0070] Dispersing nano-cesium tungsten bronze in polyvinyl alcohol aqueous solution;

[0071] The polymer quantum dots prepared by the controlled degradation of polyvinyl alcohol aqueous solution are in-situ coated on the surface of nano-cesium tungsten bronze to obtain the coated structure.

[0072] (3) Additives, 0.4-1 parts, including antioxidants and lubricants, the mass ratio of antioxidants to lubricants is (1-3):1.

[0073] The antioxidant includes at least one of antioxidant 1076, antioxidant 1098 and antioxidant 168; the lubricant includes at least one of calcium stearate, zinc stearate and magnesium stearate.

[0074] In view of the two different ways of forming the shielding compound, the preparation method of the near-infrared light-transmitting dimming material with adjustable shielding wavelength of the present invention also includes two specific preparation paths:

[0075] Preparation route 1, preparing polymer quantum dots and modified nano-cesium tungsten bronze separately, and then mixing and compounding, includes the following steps:

[0076] S1: Preparation of shielding compound:

[0077] Step 1, dissolving PVA in deionized water to obtain a clear and transparent PVA solution, wherein the PVA concentration is 0.5-1.5 wt%;

[0078] Step 2, adding the PVA solution into a high-pressure reactor, sealing the high-pressure reactor and placing it in a muffle furnace, heating it to 200-250° C. at a rate of 2-5° C. / min, isothermally reacting for 5-8 hours and then cooling it down;

[0079] Step 3: Concentrating and drying by rotary evaporator to obtain polymer quantum dot powder;

[0080] Step 4: using a silane coupling agent to modify the nano-cesium tungsten bronze;

[0081] Step 5, mixing the polymer quantum dots and the modified nano-cesium tungsten bronze evenly to obtain the shielding compound;

[0082] S2: mixing the base resin, the additive and the shielding compound to obtain a premix;

[0083] S3: adding the premixed material into an extruder, and performing melt extrusion molding to obtain the light-transmitting dimming material.

[0084] Preparation route 2, the composite coating of the polymer quantum dots on the nano-cesium tungsten bronze, comprises the following steps:

[0085] S1: Preparation of shielding compound:

[0086] Step 1, dissolving PVA in deionized water to obtain a clear and transparent PVA solution, wherein the PVA concentration is 0.5-1.5 wt%;

[0087] Step 2: Add nano-cesium tungsten bronze to the PVA solution, stir evenly, add the solution to a high-pressure reactor, seal the reactor, place the reactor in a muffle furnace, heat the reactor to 200-250° C. at a rate of 2-5° C. / min, and isothermally react for 5-8 hours before cooling down.

[0088] When the temperature drops to 60-70°C, slowly add the silane coupling agent in proportion, mix and react, and continue stirring for 2-3 hours;

[0089] Step three, concentrating and drying by a rotary evaporator to obtain a shielding compound, wherein the shielding compound includes a coating structure formed by in-situ coating of polymer quantum dots on the surface of nano-cesium tungsten bronze, and the surface of the coating structure has a silane coupling agent modified layer.

[0090] S2: mixing the base resin, the additive and the shielding compound to obtain a premix;

[0091] S3: adding the premixed material into an extruder, and performing melt extrusion molding to obtain the light-transmitting dimming material.

[0092] Example 1

[0093] The light-transmitting dimming material of Example 1 comprises, by weight, the following raw materials:

[0094] (1) PC, 98.5 copies;

[0095] (2) A shielding compound, 1 part, comprising polymer quantum dots and nano-cesium tungsten bronze in a mass ratio of 1:0.3, wherein the particle size of the polymer quantum dots is less than 5 nm; the chemical formula of the nano-cesium tungsten bronze is Cs 0.33 WO3, with a particle size of 30-50 nm, was purchased from Jiangxi Weige Nanotechnology Co., Ltd.; the nano cesium tungsten bronze was modified by silane coupling agent KH-550.

[0096] (3) Additives, 0.5 parts, including antioxidant and lubricant, the weight ratio of antioxidant to lubricant is 1:1, the antioxidant is a compound of antioxidant 1076 and antioxidant 168 in a weight ratio of 1:1; the lubricant is calcium stearate.

[0097] The preparation method of the light-transmitting dimming material adopts preparation route 1, comprising the following steps:

[0098] S1: preparing a shielding compound, comprising the following steps:

[0099] Step 1: dissolving PVA in 95° C. deionized water under magnetic stirring to obtain a clear and transparent PVA solution with a PVA concentration of 1 wt %;

[0100] Step 2: Add the PVA solution into a high-pressure reactor, seal the reactor and place it in a muffle furnace, heat it to 220° C. at 3° C. / min, react isothermally for 6 hours and then cool it down naturally to obtain a light yellow transparent solution;

[0101] Step 3: Concentrating and drying by rotary evaporator to obtain polymer quantum dot powder;

[0102] Step 4: The nano cesium tungsten bronze is modified by KH-550 silane coupling agent;

[0103] Step 5, mixing the polymer quantum dots and the modified nano-cesium tungsten bronze uniformly in proportion to obtain the shielding compound;

[0104] S2: mixing the base resin, the additive and the shielding compound to obtain a premix;

[0105] S3: adding the premixed material into an extruder, and performing melt extrusion molding to obtain a light-transmitting dimming sheet with a thickness of 1.5 mm.

[0106] Example 2

[0107] The difference between this embodiment and embodiment 1 is that the raw material ratio of the light-transmitting dimming material is different. The raw material ratio of this embodiment is:

[0108] (1) PC, 97.5 copies;

[0109] (2) shielding compound, 1.5 parts;

[0110] (3) Additives, 1 part.

[0111] The material types, proportions and preparation methods of each raw material component are the same as those in Example 1.

[0112] Example 3

[0113] The difference between this embodiment and embodiment 1 is that the raw material ratio of the light-transmitting dimming material is different. The raw material ratio of this embodiment is:

[0114] (1) PC, 99.1 parts;

[0115] (2) shielding compound, 0.5 part;

[0116] (3) Additives, 0.4 parts.

[0117] The material types, proportions and preparation methods of each raw material component are the same as those in Example 1.

[0118] Example 4

[0119] The difference between this embodiment and embodiment 1 is that in the shielding compound, the mass ratio of polymer quantum dots to nano-cesium tungsten bronze is different, and the mass ratio of polymer quantum dots to nano-cesium tungsten bronze is 1:0.01.

[0120] Example 5

[0121] The difference between this embodiment and embodiment 1 is that in the shielding compound, the mass ratio of polymer quantum dots to nano-cesium tungsten bronze is different, and the mass ratio of polymer quantum dots to nano-cesium tungsten bronze is 1:0.5.

[0122] Example 6

[0123] The difference between this embodiment and embodiment 1 is that polymer quantum dots are used to coat nano-cesium tungsten bronze to prepare the shielding compound, that is, the sample of this embodiment is obtained by using preparation route 2, which specifically includes the following steps:

[0124] S1: Preparation of shielding compound:

[0125] Step 1: Under magnetic stirring, PVA is dissolved in 95° C. deionized water to obtain a clear and transparent PVA solution with a PVA concentration of 1 wt %;

[0126] Step 2: Add nano-cesium tungsten bronze to the PVA solution, stir evenly, add the solution to the autoclave, seal the autoclave and place it in a muffle furnace, heat it to 220°C at a rate of 3°C / min, and cool it down naturally after isothermal reaction for 6 hours;

[0127] When the reactor temperature drops to 70°C, slowly add the silane coupling agent according to the proportion, mix and react, and continue stirring for 3 hours;

[0128] Step three: concentrate and dry by rotary evaporator to obtain a shielding compound with a particle size of less than 65 nm, wherein the shielding compound includes a coating structure formed by in-situ coating of polymer quantum dots on the surface of nano-cesium tungsten bronze, and a silane coupling agent modified layer on the outer surface of the coating structure.

[0129] Example 7

[0130] The difference between this embodiment and embodiment 6 is that in the shielding compound, the mass ratio of polymer quantum dots to nano-cesium tungsten bronze is different, and the mass ratio of polymer quantum dots to nano-cesium tungsten bronze is 1:0.01.

[0131] Example 8

[0132] The difference between this embodiment and embodiment 6 is that in the shielding compound, the mass ratio of polymer quantum dots to nano-cesium tungsten bronze is different, and the mass ratio of polymer quantum dots to nano-cesium tungsten bronze is 1:0.5.

[0133] Example 9

[0134] The difference between this embodiment and embodiment 6 is that this embodiment obtains a light-transmitting dimming sheet with a thickness of 2.5 mm through melt extrusion molding.

[0135] Example 10

[0136] The difference between this embodiment and embodiment 6 is that the process conditions for preparing the shielding compound are changed, and specifically include the following steps:

[0137] S1: Preparation of shielding compound:

[0138] Step 1: Under magnetic stirring, PVA is dissolved in 95° C. deionized water to obtain a clear and transparent PVA solution with a PVA concentration of 1 wt %;

[0139] Step 2: Add nano-cesium tungsten bronze to the PVA solution, stir evenly, add the solution to the autoclave, seal the autoclave and place it in a muffle furnace, heat it to 210°C at a rate of 3°C / min, and cool it down naturally after isothermal reaction for 5 hours;

[0140] When the reactor temperature drops to 70°C, slowly add the silane coupling agent according to the proportion, mix and react, and continue stirring for 3 hours;

[0141] Step three, concentrating and drying by rotary evaporator to obtain a shielding compound with a particle size below 70 nm, wherein the shielding compound includes a coating structure formed by in-situ coating of polymer quantum dots on the surface of nano-cesium tungsten bronze, and a silane coupling agent modified layer on the outer surface of the coating structure.

[0142] Embodiment 11

[0143] The difference between this embodiment and embodiment 6 is that the process conditions for preparing the shielding compound are changed, and specifically include the following steps:

[0144] S1: Preparation of shielding compound:

[0145] Step 1: Under magnetic stirring, PVA is dissolved in 95° C. deionized water to obtain a clear and transparent PVA solution with a PVA concentration of 1 wt %;

[0146] Step 2: Add nano-cesium tungsten bronze to the PVA solution, stir evenly, add the solution to the autoclave, seal the autoclave and place it in a muffle furnace, heat it to 240°C at a rate of 5°C / min, and cool it down naturally after isothermal reaction for 7 hours;

[0147] When the reactor temperature drops to 70°C, slowly add the silane coupling agent according to the proportion, mix and react, and continue stirring for 3 hours;

[0148] Step three: concentrate and dry by rotary evaporator to obtain a shielding compound with a particle size below 62 nm, wherein the shielding compound includes a coating structure formed by in-situ coating of polymer quantum dots on the surface of nano-cesium tungsten bronze, and a silane coupling agent modified layer on the outer surface of the coating structure.

[0149] Comparative Example 1

[0150] The difference between this comparative example and Example 1 is that only polymer quantum dots are used in the shielding compound of this comparative example, and modified nano cesium tungsten bronze is not used.

[0151] Comparative Example 2

[0152] The difference between this comparative example and Example 1 is that only modified nano-cesium tungsten bronze is used in the shielding compound of this comparative example, and polymer quantum dots are not used.

[0153] Comparative Example 3

[0154] The difference between this comparative example and Example 1 is that the content of the shielding compound in this comparative example is too high (about 2%), and the types and proportions of materials in the shielding compound and additives are the same as those in Example 1.

[0155] Comparative Example 4

[0156] The difference between this comparative example and Example 1 is that the content of the shielding compound in this comparative example is too low (about 0.4%), and the types and proportions of materials in the shielding compound and additives are the same as those in Example 1.

[0157] The main materials in Examples 1-11 and Comparative Examples 1-4 are shown in Table 1, wherein the particle sizes of polymer quantum dots and shielding compound were analyzed using BeNano 90Zeta nanoparticle size and Zeta potential analyzer, and the TEM photos of polymer quantum dots are shown in Figure 1 .

[0158] Table 1 Main materials in Examples 1-11 and Comparative Examples 1-4

[0159]

[0160] The overall particle size of polymer quantum dots prepared by controlled degradation of polyvinyl alcohol aqueous solution can be controlled below 5nm. Through a large number of experiments, the main factors affecting the particle size of polymer quantum dots are the temperature and reaction time of isothermal reaction in the muffle furnace. The higher the temperature and the longer the time, the smaller the particle size of the obtained polymer quantum dots. The same trend also exists when the polymer quantum dots are in situ coated with nano-cesium tungsten bronze, and the particle size of the coated structure is different under the same conditions. The secondary influencing factor is the heating rate. After exploration, the particles are more uniform and the difference is small when the temperature is raised to the reaction temperature at a rate of 2 to 5℃ / min. If the speed is too small or too large, it is easy to cause the particle size uniformity to deteriorate, affecting the light transmission dimming performance and mechanical properties.

[0161] The sheet samples obtained in Examples 1-11 and Comparative Examples 1-4 were tested for light transmittance using an LS182 solar film tester. The test results are shown in Table 2. The transmittance curves of Examples 1, 6 and 7 are shown in Table 2. Figure 2-4 .

[0162] Table 2 Light transmittance test results of samples of Examples 1-11 and Comparative Examples 1-4

[0163]

[0164]

[0165] From Table 2 and Figure 2-4 It can be seen that although there are differences in the light transmittance of the sheet samples of Examples 1-11, their visible light transmittance is all below 30%, the near-infrared light transmittance is above 45%, and the initial transmission wavelength is adjustable from 700nm to 1200nm. The samples of Examples 6-11 can ensure complete visible light shielding below 700nm, and can basically shield full-wavelength visible light below 800nm ​​to avoid interference with near-infrared detection. The aforementioned embodiments provide a variety of light transmission and dimming schemes by adjusting the composition, proportion and preparation process of the shielding compound. These schemes can be used directly as needed, or the shielding compounds involved in the various schemes can be combined to further formulate the required light transmission and dimming strategies to meet the application scenarios of various near-infrared light transmission and dimming materials. In comparison, the light transmission performance of Comparative Examples 1-4 is difficult to take into account both high visible light shielding and high near-infrared transmittance.

[0166] The tensile strength and elongation at break were tested according to ASTM D882 standard. The test results are shown in Table 3.

[0167] Table 3 Mechanical properties test results of samples of Examples 1-11 and Comparative Examples 1-4

[0168]

[0169]

[0170] The tensile strength of the sheet samples of Examples 1-11 is all above 55MPa, preferably above 60MPa, and the elongation at break is all above 80%, preferably above 90%. The light-transmitting dimming material has low visible light transmittance, high near-infrared light transmittance, wide light transmittance adjustability, and excellent mechanical properties and processing properties. It can be used as a filter material for infrared sensors and infrared cameras, and can also be widely used in applications such as automobiles and smart home appliances.

[0171] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concepts. Therefore, the present invention is intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention.

Claims

1. A near-infrared light-transmitting dimming material with adjustable shielding wavelength, characterized in that: The light-transmitting dimming material comprises, by weight: Base resin 97.5~99.1 parts Shielding compound 0.5-1.5 parts Additives 0.4~1 part The shielding compound comprises polymer quantum dots and nano-cesium tungsten bronze, and the mass ratio of the polymer quantum dots to the nano-cesium tungsten bronze is 1:(0.01-0.5); The visible light transmittance of the light-transmitting dimming material is below 30%, the near-infrared light transmittance is above 45%, and the initial transmission wavelength is adjustable from 700nm to 1200nm.

2. The light-transmitting dimming material according to claim 1, characterized in that: The matrix resin includes at least one of PP, PMMA and PC; The auxiliary agent includes an antioxidant and a lubricant, and the mass ratio of the antioxidant to the lubricant is (1-3):

1.

3. The light-transmitting dimming material according to claim 1 or 2, characterized in that: Nano cesium tungsten bronze chemical formula Cs x WO3, 0 < x ≤ 0.33, particle size is 10 - 50 nm; The nano cesium tungsten bronze may be optionally modified by a silane coupling agent.

4. The light-transmitting dimming material according to claim 3, characterized in that: The polymer quantum dots were prepared by controlled degradation of polyvinyl alcohol aqueous solution, with a particle size below 5 nm; The nano cesium tungsten bronze is modified by a silane coupling agent; The polymer quantum dots and the modified nano-cesium tungsten bronze are mixed evenly to obtain the shielding compound.

5. The light-transmitting dimming material according to claim 3, characterized in that: The shielding compound includes a coating structure formed by coating polymer quantum dots on the surface of nano-cesium tungsten bronze, and the coating structure is obtained by the following steps: Dispersing nano-cesium tungsten bronze in polyvinyl alcohol aqueous solution; The polymer quantum dots prepared by the controlled degradation of polyvinyl alcohol aqueous solution are in-situ coated on the surface of nano-cesium tungsten bronze to obtain the coated structure.

6. A method for preparing the light-transmitting dimming material according to any one of claims 1 to 5, characterized in that: The steps include: S1: preparing a shielding compound; S2: mixing the base resin, the additive and the shielding compound to obtain a premix; S3: adding the premixed material into an extruder, and performing melt extrusion molding to obtain the light-transmitting dimming material.

7. The preparation method according to claim 6, characterized in that: S1 includes the following steps: Step 1, dissolving PVA in deionized water to obtain a clear and transparent PVA solution; Step 2: Add the PVA solution into a high-pressure reactor, seal the reactor and place it in a muffle furnace, heat it to 200-250° C., react isothermally for 5-8 hours and then cool it down; Step 3: Concentrating and drying by rotary evaporator to obtain polymer quantum dot powder; Step 4: using a silane coupling agent to modify the nano-cesium tungsten bronze; Step 5: Evenly mix the polymer quantum dots and the modified nano-cesium tungsten bronze to obtain the shielding compound.

8. The preparation method according to claim 6, characterized in that: In the shielding compound, the polymer quantum dots cover at least a portion of the nano-cesium tungsten bronze, and S1 comprises the following steps: Step 1, dissolving PVA in deionized water to obtain a clear and transparent PVA solution; Step 2: Add nano-cesium tungsten bronze to the PVA solution, stir evenly, add the solution to a high-pressure reactor, seal the reactor, place it in a muffle furnace, heat it to 200-250° C., react isothermally for 5-8 hours, and then cool it down; Step 3: Concentrate and dry by rotary evaporator to obtain a shielding compound, wherein the shielding compound includes a coating structure formed by in-situ coating of polymer quantum dots on the surface of nano-cesium tungsten bronze.

9. The preparation method according to claim 7 or 8, characterized in that: In step 2, the temperature is raised to 200-250° C. at a rate of 2-5° C. / min.

10. The preparation method according to claim 8, characterized in that: The cooling process of step 2 also includes adding a silane coupling agent at 60-70° C. and mixing and reacting to make the surface of the coating structure have a silane coupling agent modified layer.